Trophic position and dietary breadth of bats revealed by nitrogen isotopic composition of amino acids. Issue 1 (December 2017) - Campbell, Caitlin; Nelson, David; Ogawa, Nanako; Chikaraishi, Yoshito; Ohkouchi, Naohiko
Abstract Bats perform important ecosystem services, but it remains difficult to quantify their dietary strategies and trophic position (TP)in situ . We conducted measurements of nitrogen isotopes of individual amino acids (δ 15 NAA ) and bulk-tissue carbon (δ 13 Cbulk ) and nitrogen (δ 15 Nbulk ) isotopes for nine bat species from different feeding guilds (nectarivory, frugivory, sanguivory, piscivory, carnivory, and insectivory). Our objective was to assess the precision ofδ 15 NAA -based estimates of TP relative to other approaches. TPs calculated fromδ 15 N values of glutamic acid and phenylalanine, which range from 8.3–33.1‰ and 0.7–15.4‰ respectively, varied between 1.8 and 3.8 for individuals of each species and were generally within the ranges of those anticipated based on qualitative dietary information. Theδ 15 NAA approach reveals variation in TP within and among species that is not apparent fromδ 15 Nbulk data, andδ 15 NAA data suggest that two insectivorous species (Lasiurus noctivagans andLasiurus cinereus ) are more omnivorous than previously thought. These results indicate that bats exhibit a trophic discrimination factor (TDF) similar to other terrestrial organisms and thatδ 15 NAA provides a reliable approach for addressing questions about variation in the TP of bats that have heretofore proven elusive.